PERSPEKTIF RASUL PAULUS TENTANG BERBAHASA ROH BERDSARKAN 1 KORINTUS 14 - Daniel Sarwono (Sekolah Tinggi Teologi Arastamar Bengkulu, 2015)
The gift of speaking in tongues is a message to the body of Christ which is given in tongues and is not understood by the user. Therefore, it must be followed by an interpretation by the language understood by the congregation. The gift of tongues is usually news of a prophecy for the Lord's church and must be followed by an interpretation. If the gift of tongues is not followed by an interpretation, it cannot build up the church. Therefore, the author will discuss the apostle Paul's perspective on tongues based on 1 Corinthians 14.